Antibiotics Tubes and Lines - Khurana, Navpreet; Salei, Aliaksei; Gunn, Andrew J.; Huang, Junjian (Seminars in Interventional Radiology, 2022)
Antibiotic prophylaxis in interventional radiology (IR) is widely used; however, such practice is based on data from the surgical literature. Although published guidelines can help determine the need for prophylactic antibiotic use in the patient undergoing percutaneous procedures, local practice patterns often dictate when such medications are given. In this article, the current state of periprocedural antibiotic use in commonly performed IR procedures (i.e., tube and catheter placements) is presented.
Keywords: interventional radiology; infection; antibiotic; prophylaxis